2013
DOI: 10.1021/jf304071n
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Transgenic Potato Tubers Expressing Arabidopsis Dehydration Response Element-Binding Protein 1A (DREB1A)

Abstract: Untargeted metabolome analyses play a critical role in understanding possible metabolic fluctuations of crops under varying environmental conditions. This study reports metabolic profiles of transgenic potato tubers expressing the Arabidopsis DREB1A transcription factor gene, which induces expression of genes involved in environmental stress tolerance. A combination of targeted and untargeted metabolomics demonstrated considerable metabolome differences between the transgenic lines and nontransgenic parent cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 49 publications
(116 reference statements)
0
20
0
Order By: Relevance
“…As mentioned above, these factors can be used to improve drought tolerance in a variety of crops. Our group has utilized these key TFs for the improvement of drought tolerance in crops including rice, wheat, and soybean in collaboration with international and domestic institutes (Pellegrineschi et al, 2004; Hong et al, 2006; Behnam et al, 2007; Bhatnagar-Mathur et al, 2007; Polizel et al, 2011; Datta et al, 2012; Ishizaki et al, 2012; Saint Pierre et al, 2012; Barbosa et al, 2013; Bhatnagar-Mathur et al, 2013; de Paiva Rolla et al, 2013; Engels et al, 2013; Iwaki et al, 2013). Some results using crops including rice and peanut have shown that stress-specific overexpression of DREB1A improves drought tolerance and grain yield compared with controls in the field (Datta et al, 2012; Bhatnagar-Mathur et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, these factors can be used to improve drought tolerance in a variety of crops. Our group has utilized these key TFs for the improvement of drought tolerance in crops including rice, wheat, and soybean in collaboration with international and domestic institutes (Pellegrineschi et al, 2004; Hong et al, 2006; Behnam et al, 2007; Bhatnagar-Mathur et al, 2007; Polizel et al, 2011; Datta et al, 2012; Ishizaki et al, 2012; Saint Pierre et al, 2012; Barbosa et al, 2013; Bhatnagar-Mathur et al, 2013; de Paiva Rolla et al, 2013; Engels et al, 2013; Iwaki et al, 2013). Some results using crops including rice and peanut have shown that stress-specific overexpression of DREB1A improves drought tolerance and grain yield compared with controls in the field (Datta et al, 2012; Bhatnagar-Mathur et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the function of the DREB1/CBF regulon in the regulation of cold stress responses is widely conserved in angiosperms. Overexpression of DREB/CBF TFs has been reported to enhance drought tolerance in transgenic crops including chrysanthemum (Hong et al, 2006), peanut (Bhatnagar-Mathur et al, 2007, Bhatnagar-Mathur et al, 2013), potato (Behnam et al, 2007; Iwaki et al, 2013), rice (Oh et al, 2005; Ito et al, 2006; Datta et al, 2012), soybean (Polizel et al, 2011; de Paiva Rolla et al, 2013), tobacco (Kasuga et al, 2004), tomato (Hsieh et al, 2002a,b), and wheat (Pellegrineschi et al, 2004; Saint Pierre et al, 2012). For example, rice DREB1/CBF-type TFs involved in cold-responsive gene expression also conferred improved tolerance to drought in transgenic rice (Ito et al, 2006).…”
Section: Dreb1/cbf Tfs For Cold-responsive Gene Expression To Improvementioning
confidence: 99%
“…This approach has already revealed a more comprehensive and holistic framework for presenting possible compositional differences between transgenic and conventionally bred plants [13,14]. Furthermore, it has helped to identify unfavorable metabolites, including toxic compounds, or any unintended metabolic changes due to such genetic modifications [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The l -3-cyanoalanine content of the maximum dose of MucoRice-CTB (6 g) is thus estimated to be 5.7 μg. The l -3-cyanoalanine content in MR-CTB51A brown rice (956 ng g −1 DW) is lower than that in non-transgenic potato tubers (1.8 μg g −1 fresh weight) 26 . No serious adverse responses have been attributed to daily rice consumption 43 .…”
Section: Discussionmentioning
confidence: 73%